Analisis Kelayakan Lembar Kerja Mahasiswa (LKM) Untuk Menunjang Perkuliahan Fisika Inti pada Materi Reaksi Fisi Nuklir - Rizka Nabila; Hidayati Hidayati; Silvi Yulia Sari (Universitas Negeri Padang, 2018)
The process of nuclear physics learning at this time has not fulfilled the desired learning outcomes. Based on the observations, most of the nuclear physics topic is abstract and nuclear physics learning has not been supported by laboratory activities. The solution of this problem is to do laboratory activities with virtual laboratory activities. The application that will be used in this activity requires a guide that matches the characteristics of students. This research aims to develop valid and practice student worksheets (LKM) as a support for virtual laboratory activities on the topic of nuclear fission reactions. The LKM was developed using the ADDIE method that is limited to the development stage. The object of this research is an LKM used as support for virtual laboratory activities. The data collection instrument used in this research is a validity questionnaire and practicality questionnaire. Based on the research that has been done, the conclusion is the LKM has been valid and practice to be used in the nuclear physics learning on the topic of nuclear fission reactions.